Influence of non-thermal argon plasma needle on blood coagulation - Aadim, Kadhim A. (Iraqi Journal of Physics, 2019)
Non-thermal argon plasma needle at atmospheric pressure was constructed. The experimental setup was based on a simple and low cost electric component that generates a sufficiently high electric field at the electrodes to ionize the argon gas which flow at atmospheric pressure. A high AC power supply was used with 1.1 kV and 19.57 kHz. Non-thermal Argon plasma used on blood samples to show the ability of non-thermal plasma to promote blood coagulation. Three tests have been done to show the ability of plasma to coagulate both normal and anti-coagulant blood. Each blood sample has been treated for varying time from 20sec. to 180sec. at different distances. The results of the current study showed that the cold plasma produced from argon significantly increase the in vitro speed of blood coagulation, the plasma increases activation and aggregation of platelets, causes proliferation of fibroblasts and fibrin production accelerates blood coagulation.